2013
DOI: 10.1002/mbo3.86
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of type IV pilin induces mucoidy in Pseudomonas aeruginosa strain PAO579

Abstract: Pseudomonas aeruginosa is a Gram negative, opportunistic pathogen that uses the overproduction of alginate, a surface polysaccharide, to form biofilms in vivo. Overproduction of alginate, also known as mucoidy, affords the bacterium protection from the host's defenses and facilitates the establishment of chronic lung infections in individuals with cystic fibrosis. Expression of the alginate biosynthetic operon is primarily controlled by the alternative sigma factor AlgU (AlgT/σ22). In a nonmucoid strain, AlgU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In this study, we demonstrated that the truncated pilin PilA 108 with the FTF motif at its carboxyl terminus (Withers et al 2013), and this is the first trial to activate AlgW by another protein in vitro. This demonstrated intuitionally the possibly real reaction in the cell.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In this study, we demonstrated that the truncated pilin PilA 108 with the FTF motif at its carboxyl terminus (Withers et al 2013), and this is the first trial to activate AlgW by another protein in vitro. This demonstrated intuitionally the possibly real reaction in the cell.…”
Section: Discussionmentioning
confidence: 70%
“…In vivo genetic analyses suggested that PilA 108 might cause the mucoid conversion through AlgW activation (Withers et al 2013), but we had no idea whether PilA 108 acted directly on AlgW. Moreover, the use of a purified protein to activate AlgW to cleave MucA directly in vitro has never been reported.…”
Section: Pila 108 Activates Algw To Cleave Muca Perimentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the mucoid phenotype, the strain C7447m has wild-type algU and mucA . Furthermore, among previously reported alginate production-related genes (36), the amino acid sequences of MucC, MucD, AlgL, and KinB each have 1 amino acid change; AlgX has 2 amino acid changes; and AlgI and AlgP have 5 amino acid changes. We also found some SNPs located in the intergenic region before algB , algC , algD , amrZ , clpP2 , mucE , mucR , and pilA .…”
Section: Genome Announcementmentioning
confidence: 92%
“…with fibrosis patients). [13][14][15] This mucoid strain is characterized by the overproduction of alginate polysaccharides, which are copolymers of 1-4 linked D-mannuronic and L-guluronic acid residues. 16 The adhesion of mucoid alginate to the lung of patient is a major virulence factor that causes a series of problems including hosting dormant bacteria, reducing the effectiveness of antibiotics, and difficulty in breathing.…”
mentioning
confidence: 99%